Effect of Ce dopant on upconversion and temperature sensing performances in homogeneous ultrasmall Y2O3:Yb3+/Ho3+ nanoparticles through flame aerosol synthesis. Issue 7 (1st April 2023) - Hu, Shuai; Yuan, Maohui; Huang, Hanchang; Song, Changqing; Han, Kai; Cui, Wenda; Yang, Zining; Wang, Hongyan
Abstract: Flame aerosol synthesis (FAS) is an excellent strategy for continuous, fast, and mass production of small-size upconversion nanoparticles (UCNPs), which have high potential applications in fields like biological imaging, colour display and optical temperature sensing. However, flame-made UCNPs have received less attention, and relevant studies are limited. Herein, for the first time, we successfully fabricated cerium (Ce)-doped homogeneous ultrasmall Y2 O3 :Yb 3+ /Ho 3+ UCNPs using a liquid-fed FAS method. Ce was doped to improve the upconversion luminescence (UCL) of the Y2 O3 :Yb 3+ /Ho 3+ UCNPs. The overall UCL intensity was enhanced ∼77.9-fold for an optimal concentration of 20 mol% Ce-doped UCNPs, compared with the UCNPs without Ce doping with a relatively homogeneous ultrasmall size of 8–10 nm. Further studies confirmed that both trivalent (Ce 3+ ) and tetravalent (Ce 4+ ) simultaneously exist in the Y2 O3 hosts and are critical in enhancing the UCL properties. In addition, the fluorescence intensity ratio (FIR) method was used to evaluate the thermal properties of the fabricated UCNPs. Ce doping significantly improved the thermal sensitivity of Y2 O3 :Yb 3+ /Ho 3+ UCNPs. An excellent relative sensitivity ( S R ) of 0.622% K −1 at 598 K was obtained for flame-made UCNPs doped with 20 mol% Ce.